Rediscovery and redescription of a sponge-associated axiid shrimp, Eiconaxius acutifrons Bate, 1888 (Crustacea: Decapoda: Axiidea) - Komai, Tomoyuki; Tsuchida, Shinji (Zootaxa, 2012)
A poorly known deep-water axiid shrimp, Eiconaxius acutifrons Bate, 1888, the type species of the genus, is redescribedon the basis of the two type specimens (lectotype and paralectotype, designated herein) from the Banda Sea, Indonesia,and three recently collected specimens from the Myojin Knoll, Izu Islands, Japan. Diagnostic characters of this speciesare reassessed, and the comparison with closely allied congeneric species is made. Previous records referred to E.acutifrons are reviewed. It has been confirmed that none of the subsequent records under the name represent the true E.acutifrons. We found that Eiconaxius albatrossae Kensley, 1996 and E. faxoni Sakai, 2011 were based on the same seriesof material from the eastern Pacific, referred to E. acutifrons by Faxon (1895), but the Sakai’s (2011) taxon name is unavailable because of the lack of an explicit type fixation.